An Exploratory Study for Improving the Housing Situation of Korean ElderlyBased on the Opinions of Housing Researchers and Welfare Facility Staff. Issue 3 (1st September 2017) - Kwon, Ohjung; Kim, Dongsook; Kim, Jinyoung
Abstract : The elderly population in Korea has dramatically increased in recent decades. Since 1970, it has increased by 342%. In addition, housing needs of the elderly are becoming more diverse than in the past, in terms of household types, economic status, health status, education level, family relationships, and housing experiences throughout their lifetimes. Seniors expect to live in a housing option appropriate to their preferences. In reality, however, there is a lack of sufficient housing alternatives to suit their needs. Thus, various housing alternatives need to be developed to allow Korean seniors to live as they want. This study surveyed the opinions of researchers and facility staff in the field of elderly housing to identify the opinions of residents-related characteristics and to investigate current problems/difficulties and improvement needs of the social, physical, and management aspects. It can be useful information that can facilitate the development of alternative plans for elderly housing in the future. A questionnaire with open-ended questions was distributed to 50 housing researchers and facility staff members.